Filtriranje zraka in razvoj obraznih mask iz nanovlaken za zaščito pred virusi - Gostiša, Maruša (Farmacevtski vestnik, 2021)
Air-particle pollution and the covid-19 pandemic have resulted in a huge global need for specific and effective measures to protect human health. Membrane filtration is now considered the most efficient and reliable physical method against air pollutants, although face masks with filters with high quality factors and antiinfective properties are still a challenge for mask manufacturers and consumers. here we provide a basic description for a broader understanding of respiratory protection, covering types of particles in the air, filtration mechanisms and testing of the filter effectiveness, along with the types of face masks and offered protection performance. We then look into the near future, where the greatest interest is for the development of new filters and face masks to remove viruses, which can be achieved above all through nanotechnological approaches.
Keywords: delci v zraku; Diagnostika; Nanotehnologija; obrazna maska; Onesnaženost; učinkovitost filtriranja delcev; Zaščitne maske